2021
DOI: 10.1016/j.ijpara.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Replication and partitioning of the apicoplast genome of Toxoplasma gondii is linked to the cell cycle and requires DNA polymerase and gyrase

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The most highly enriched PfHO-specific interactor in both IP/MS experiments was an unannotated protein (Pf3D7_1025300) that contains a putative aspartyl protease domain and shows distant structural similarity to DNA damage-inducible protein (Ddi-1, P40087) -a ubiquitin-dependent protease associated with transcription factor processing [59][60][61] (Figure 5 -figure supplement 2). These putative interactors are consistent with reports of non-canonical HO roles in gene expression [62][63][64] , retention by mature PfHO of an electropositive N-terminus favorable for interacting with nucleic acids (Figure 4B), and apparent PfHO localization to the membrane periphery of the apicoplast lumen (Figure 3B) where the apicoplast genome, DNA replication factors, and ribosomes associate [65][66][67] . We thus considered it most likely that PfHO had an essential function in either apicoplast genome replication or DNA-dependent gene expression.…”
Section: Figure Supplement 1 Sequence Homologs Of Pfho Based On Blastsupporting
confidence: 89%
“…The most highly enriched PfHO-specific interactor in both IP/MS experiments was an unannotated protein (Pf3D7_1025300) that contains a putative aspartyl protease domain and shows distant structural similarity to DNA damage-inducible protein (Ddi-1, P40087) -a ubiquitin-dependent protease associated with transcription factor processing [59][60][61] (Figure 5 -figure supplement 2). These putative interactors are consistent with reports of non-canonical HO roles in gene expression [62][63][64] , retention by mature PfHO of an electropositive N-terminus favorable for interacting with nucleic acids (Figure 4B), and apparent PfHO localization to the membrane periphery of the apicoplast lumen (Figure 3B) where the apicoplast genome, DNA replication factors, and ribosomes associate [65][66][67] . We thus considered it most likely that PfHO had an essential function in either apicoplast genome replication or DNA-dependent gene expression.…”
Section: Figure Supplement 1 Sequence Homologs Of Pfho Based On Blastsupporting
confidence: 89%
“…To distinguish between these possibilities, LAP body structure was examined in dividing parasites by high resolution Airyscan confocal imaging with the modification that GRA3 replaced YFP-SidM-P4M as LAP body marker. In RH-WT parasites, GRA3-positive DGs were distributed throughout the cell during the initiation of mitosis as landmarked by the elongation of the apicoplast (asterisk in Figure 8Ci ; Martins-Duarte et al, 2021). By contrast, parasites expressing YFP-SidM-P4M during the initiation of cell division exhibited a GRA3-positive LAP body ( Figure 8Cii ).…”
Section: Resultsmentioning
confidence: 99%
“…In T . gondii , TgTPC is exclusively found in the apicoplast, an endosymbiotic organelle that harbors multiple metabolic pathways required for parasite division [ 252 254 ]. Li and colleagues showed that TgTPC is needed for proper formation of apicoplast-ER contact sites and seems to mediate the transference of Ca 2+ between these organelles [ 57 ].…”
Section: Ion Channel Repertoiresmentioning
confidence: 99%